The effect of surface treatment and post-length on fiber post-bond strength - Stevan Untono; Ade Prijanti Dwisaptarini; Aryadi Subrata; Rosalina Tjandrawinata (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Endodontically treated teeth with extensive loss structure may require a post. Fiber post is made of a resin polymer matrix held by epoxy resin, which has a high conversion rate and high cross-linking, which may not interact with the monomer of resin cement that can reduce the bond strength that may cause post-debonding, which is a common failure of fiber post. Post-surface treatment and post-length are factors that affect post-bond strength. Objective: This study aims to determine the effect of surface treatment on fiber post and post-length on the bond strength of fiber post. Materials and Methods: Thirty mandibular premolars were selected, decoronated 15 mm from the coronal to the apical region, and then subjected to root canal treatment, obturation, and post-preparation. The samples were initially divided into two groups; each was assigned to a specific post-length; then, each group was randomly divided into a negative control group, air abrasion group, and laser group, for a total of six groups (n = 5). Self-adhesive resin cement is used for post-cementation. Selfadhesive resin cement is used for post-cementation. The evaluation of fiber postbond strength in this study was evaluated with the pull-out test using a universal testing machine at a speed of 0.5 mm/min. Data were analyzed by two-way ANOVA and Tukey’s test. Results: The air abrasion group showed a higher bond strength (P < 0.05) compared with the control and Er:Cr:YSGG laser groups. No significant difference in bond strength was observed between the control and Er:Cr:YSGG laser groups with both post-lengths. Moreover, post-length had no effect on bond strength, and no significant interaction was found between surface treatment and post-length. Conclusion: In this study, the bond strength was higher with surface treatment by air abrasion. Post-length had no impact on bond strength.